2020
DOI: 10.46475/aseanjr.v21i3.81
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal CT radiation dose reduction at Siriraj Hospital (Phase II)

Abstract: Objective: To compare radiation dose, radiologists’ satisfaction, and image noise between the standard dose abdominal CT currently performed at our hospital and the new automatic tube current modulation (ATCM) low dose abdominal CT, using various parameters (0%, 10%, 20%, and 30%) of the Adaptive Statistical Iterative Reconstruction (ASiR). Materials and Methods: We prospectively performed the ATCM low dose abdominal CT in 111 participants who had prior standard dose CT for comparison. The ATCM low dose CT ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Our ndings align with previous studies [30,32,35,40] that reported that higher DLIR or IR strength leads to reduced image noise. We also observed a weak to moderate positive correlation between image noise and both BMI and waist circumference, consistent with prior studies [41][42]. In overweight or obese patients, increased body circumference or thickness hinders photon penetration, resulting in elevated image noise [43][44].…”
Section: Discussionsupporting
confidence: 90%
“…Our ndings align with previous studies [30,32,35,40] that reported that higher DLIR or IR strength leads to reduced image noise. We also observed a weak to moderate positive correlation between image noise and both BMI and waist circumference, consistent with prior studies [41][42]. In overweight or obese patients, increased body circumference or thickness hinders photon penetration, resulting in elevated image noise [43][44].…”
Section: Discussionsupporting
confidence: 90%
“…In the quantitative image assessment, the image noise of the aorta and the liver on the FTC and the ATCM low dose abdominal CT were summarized in Table 3. From our previous phase I [7] and phase II [15] studies, both FTC and ATCM low dose abdominal CT provided significant radiation dose reduction compared to the standard dose CT, and at the same time offered acceptable image quality. The purpose of this current phase III study was to directly compare these two aforementioned low dose CT techniques in either image quality or radiation dose.…”
Section: Image Assessmentmentioning
confidence: 99%
“…Our phase II study [15] was prospectively performed in 111 participants, comparing low dose abdominal CT using the ATCM technique and conventional standard dose CT. The ATCM low dose CT images were post-processed on a CT workstation with 4 parameters of ASiR (0%, 10%, 20%, and 30%).…”
mentioning
confidence: 99%